Caribbean species of Eiconaxius (Decapoda: Axiidea: Axiidae) - Poore, Gary C. B. (Zootaxa, 2018)
The type status of specimens of three species of the axiid genus Eiconaxius Bate, 1888 from the Caribbean Sea is clarified. Eiconaxius agassizi Bouvier, 1905, E. borradailei Bouvier, 1905 and E. caribbaeus (Faxon, 1896) are diagnosed and illustrated. Axius (Eiconaxius) communis Bouvier, 1905, Axius (Eiconaxius) rotundifrons Bouvier, 1905, and Axius (Eiconaxius) caribbaeus carinatus Bouvier, 1925, hitherto treated as valid species, are synonymised with E. caribbaeus. Lectotypes are selected for Eiconaxius agassizi Bouvier, 1905 and Eiconaxius borradailei Bouvier, 1905.